A generalised integral quadratic method: improvement of the solution for one dimensional Volterra integral equation using particle swarm optimisation. (13th February 2006) - Zerarka, A.; Khelil, N.; Saidi, H.
In a previous work, we have introduced the generalised integral quadratic method (GIQ) to handle the Volterra's integral equations in which the interpolating points of Tchebychev have been used. In this paper the particle swarm optimisation (PSO) is considered to improve, qualitatively, the solutions. This new approach is investigated and tested with some numerical examples in the linear and nonlinear cases.